National Identity (NATID) Framework in Multi-Ethnic Affiliations Consumer Market: The Case of Malaysia (Malaysian Management Journal, 2014)
This paper examines the transferability of the national identity (NATID) framework in a multi-ethnic consumer market. Data were collected using heterogeneous purposive sampling from 403 respondents in Malaysia. This study exert also responds to the cross-cultural validation of measures used in international research whereby the authors assessed measurement invariance of the NATID dimensions construct using Malaysian and non-Malaysian samples. The analysis provided strong support for the factor structure, internal consistency, and discriminant validity on the transferability of the NATID framework on the Malaysian data sample. The result also suggested ethnic affiliations are a relevant unit of analysis and indicates that the relationship between the dimensions of NATID and overall national identity, varied across the three major ethnic groups. With reference to originality, this research is pioneering the adaptive etic approach to elicit inputs and to improve the transferability of the NATID framework.